Pengaruh Manajemen Laba Terhadap Agresivitas Pajak - Dyah Metha Nurfitriasih; Dyah Febriantina Istiqomah (Pusat P2M Politeknik Negeri Batam, 2022)
This study aims to determine the effect of earnings management on tax aggressiveness and corporate governance moderation in this relationship. Tax aggressiveness is measured using the Effective Tax Rate (ETR), while earnings management is measured by calculating the Discretionary Accruals (DACC) value. Corporate Governance includes institutional ownership, independent commissioners, and audit committees. The sample of this research is manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2020. This study uses a purposive sampling method to obtain 60 samples with several observations of 180 companies during the observation period. The results show that earnings management positively affects tax aggressiveness. This finding indicates that increasing earnings management behavior will encourage companies to tax aggressiveness. Corporate Governance can reduce the effect of earnings management on tax aggressiveness. The existence of institutional ownership, an independent board of commissioners, and an audit committee can oversee the actions and decisions taken by managers so that any actions taken do not harm the Shareholders.